Analisis Determinan Perilaku dan Lingkungan Terhadap Kejadian Gastritis pada Pelajar - Febri Endra Budi Setyawan; Laily Ira Fauziyyah (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2020)
Introduction: Gastritis is an inflamed gastric mucosa that can occur in a short, monthly, or even a year. Theincidence of gastritis in senior high school students were currently the second highest disease under ISPA. Thecondition of gastritis will indirectly disrupt the learning process and can affect the concentration of learning fromsenior high school students. The most influential determinant factors are behavior and environment. Aim of study:This study was to analyze the determinants of the incidence of gastritis in senior high school students. Method: Thedesign used in this study was observational analytic with cross sectional design. Samples of 148 senior high schoolstudents were selected using the stratified simple random sampling method. The research instrument used aquestionnaire that was distributed directly to selected samples with a nominal data scale. The data obtained werecarried out by the Lambda hypothesis test and logistic regression. Results and Discussion: The results showed thatthe determinants of behavior and environment had a weak influence (r = 0.348) on the incidence of gastritis in highschool students. The logistic regression test results showed that the determinant of behavior has an OR = 5.2 withan influential breakfast habit factor and an environmental factor having an OR = 4.4 with a study load factor thatgives an influence. Conclusion: The conclusion that can be drawn was that the behavioral factors, especially thehabit of not eating breakfast and environmental factors, are related to the burden of studies that affect senior highschool students causing gastritis. These two factors can basically be controlled by increasing promotive efforts forstudents at the senior high school so that gastritis cases can be prevented.